Long-term fiscal implications of funding assisted reproduction: a generational accounting model for Spain. Issue 2 (December 2015) - Matorras, R.; Villoro, R.; González-Domínguez, A.; Pérez-Camarero, S.; Hidalgo-Vega, A.; Polanco, C.
Abstract: The aim of this study was to assess the lifetime economic benefits of assisted reproduction in Spain by calculating the return on this investment. We developed a generational accounting model that simulates the flow of taxes paid by the individual, minus direct government transfers received over the individual's lifetime. The difference between discounted transfers and taxes minus the cost of either IVF or artificial insemination (AI) equals the net fiscal contribution (NFC) of a child conceived through assisted reproduction. We conducted sensitivity analysis to test the robustness of our results under various macroeconomic scenarios. A child conceived through assisted reproduction would contribute €370, 482 in net taxes to the Spanish Treasury and would receive €275, 972 in transfers over their lifetime. Taking into account that only 75% of assisted reproduction pregnancies are successful, the NFC was estimated at €66, 709 for IVF-conceived children and €67, 253 for AI-conceived children. The return on investment for each euro invested was €15.98 for IVF and €18.53 for AI. The long-term NFC of a child conceived through assisted reproduction could range from €466, 379 to €-9, 529 (IVF) and from €466, 923 to €-8, 985 (AI). The return on investment would vary between €-2.28 and €111.75 (IVF), and €-2.48 and €128.66 (AI) for each euro invested. The break-even point at which the financial position would begin to favour the Spanish Treasury ranges between 29 and 41 years of age. Investment in assisted reproductive techniques may lead to positive discounted future fiscal revenue, notwithstanding its beneficial psychological effect for infertile couples in Spain.